2002
DOI: 10.1507/endocrj.49.329
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Serum Anti-Myeloperoxidase Antineutrophil Cytoplasmic Antibodies (MPO-ANCA) in Patients with Graves' Disease Treated with Propylthiouracil and Thiamazole.

Abstract: Patients with Graves' disease (n = 61) treated with propylthiouracil (PTU) or thiamazole (MMI) were studied retrospectively to investigate differences in the prevalence of anti-myeloperoxidase anti-neutrophil cytoplasmic antibodies (MPO-ANCA) in relation to treatment with anti-thyroid drugs. The patients were divided into two groups: PTU-treated group (n = 32) and MMI-treated group (n = 29). There were no significant differences between the two groups in terms of age, gender distribution, or duration of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 27 publications
5
51
0
2
Order By: Relevance
“…Although in some cases, the development of anti-MPO-ANCA seems to be related to PTU treatment, only a minority of patients with thyroid disease, PTU treatment, and anti-MPO antibodies developed clinical vasculitis (211,216,217). Usually, with cessation of PTU treatment, (194) Polymorphism of CTLA-4 WG with ESRD Increases T cell activation Bartfai et al (193) Cytokine genes Polymorphism in IL-10 increase WG and MPA This Th2-type cytokine is important in B cell proliferation and differentiation but can also exert anti-inflammatory activity Murakozy et al (195) Polymorphism in IL-10 increase WG Decreases IL-10 level with loss of inhibition of Th1 responses and monocyte function Borgmann et al (197) IL-1␤ increase and IL-1R antagonist decrease PR3-ANCA with ESRD Proinflammatory genotype causes proinflammatory responses Spriewald et al (194) IFN-␥ polymorphism increase WG Increases IFN-␥ production and modulates proinflammatory responses Spriewald et al (194) IFN-␥ polymorphism increase WG with ESRD Modulates disease susceptibility Spriewald et al (194) TNF-␣ polymorphism increase WG Increases TNF-␣ production and modulates proinflammatory responses Murakozy et al (195) TGF-␤1 increase WG Proinflammatory genotype causes proinflammatory responses Csernok et al (196) TGF-␤1 increase WG and MPA Inducing angiogenesis and being strongly chemotactic, TGF-␤1 serves as a proinflammatory factor Esnault et al (174) PR3 inhibitor Homozygous and heterozygous ␣1-AT deficiency PR3-ANCA Contributes to disease induction MPO levels decreased significantly and sometimes even vanished (207,217). One case report even described a change in ANCA type in a patient with WG from PR3-ANCA to MPO-ANCA after PTU therapy and a switch back upon cessation of the therapy (218).…”
Section: Pharmacologic Inductionmentioning
confidence: 99%
“…Although in some cases, the development of anti-MPO-ANCA seems to be related to PTU treatment, only a minority of patients with thyroid disease, PTU treatment, and anti-MPO antibodies developed clinical vasculitis (211,216,217). Usually, with cessation of PTU treatment, (194) Polymorphism of CTLA-4 WG with ESRD Increases T cell activation Bartfai et al (193) Cytokine genes Polymorphism in IL-10 increase WG and MPA This Th2-type cytokine is important in B cell proliferation and differentiation but can also exert anti-inflammatory activity Murakozy et al (195) Polymorphism in IL-10 increase WG Decreases IL-10 level with loss of inhibition of Th1 responses and monocyte function Borgmann et al (197) IL-1␤ increase and IL-1R antagonist decrease PR3-ANCA with ESRD Proinflammatory genotype causes proinflammatory responses Spriewald et al (194) IFN-␥ polymorphism increase WG Increases IFN-␥ production and modulates proinflammatory responses Spriewald et al (194) IFN-␥ polymorphism increase WG with ESRD Modulates disease susceptibility Spriewald et al (194) TNF-␣ polymorphism increase WG Increases TNF-␣ production and modulates proinflammatory responses Murakozy et al (195) TGF-␤1 increase WG Proinflammatory genotype causes proinflammatory responses Csernok et al (196) TGF-␤1 increase WG and MPA Inducing angiogenesis and being strongly chemotactic, TGF-␤1 serves as a proinflammatory factor Esnault et al (174) PR3 inhibitor Homozygous and heterozygous ␣1-AT deficiency PR3-ANCA Contributes to disease induction MPO levels decreased significantly and sometimes even vanished (207,217). One case report even described a change in ANCA type in a patient with WG from PR3-ANCA to MPO-ANCA after PTU therapy and a switch back upon cessation of the therapy (218).…”
Section: Pharmacologic Inductionmentioning
confidence: 99%
“…A prevalência de ANCA-MPO nos usuários de drogas antitireoidianas varia de 25-60% nos pacientes tratados com PTU, e de 3,4% nos tratados com metimazol (29)(30)(31). Em uma análise, Sato e cols.…”
Section: Auto-imunidade Anca Por Propiltiouracilunclassified
“…Anti-thyroid drugs ANCA-associated vasculitis occurs more frequently in women, consistently with the fact that Graves' disease is more common in female gender. It has been reported that the prevalence of MPO-ANCA is higher in patients treated with PTU than in those treated with MMI (Wada et al, 2002). Thus, the prevalence of ANCA positivity has been estimated to average 26% of PTU-treated subjects (Gunton et al, 2000), being even higher in treated children (Hirokazu et al, 2000).…”
Section: Autoimmune Markers Of Thionamides-related Vasculitismentioning
confidence: 99%
“…In a retrospective study of 61 patients with Graves' disease, Wada et al reported that 25% of patients treated with PTU showed positive MPO-ANCA, unlike 3.4% of patients receiving MMI. Moreover, the sole patient MPO-ANCA positive treated with MMI had been taking PTU for six years before starting MMI treatment (Wada et al, 2002). The annual incidence of MPO-ANCA-associated vasculitis in patients treated with antithyroid drugs has been estimated to be between 0.53 and 0.79 patients per 10,000, although several mild cases may not have been reported (Noh et al, 2009).…”
Section: Autoimmune Markers Of Thionamides-related Vasculitismentioning
confidence: 99%